Slow-sculpting graphene oxide/alginate gel loaded with platelet-rich plasma to promote wound healing in rats - Chen, Ningjie; Li, Mengjie; Yang, Jincun; Wang, Peng; Song, Guodong; Wang, Haitao (Frontiers in Bioengineering and Biotechnology, 2024)
Abstract: Wounds, especially chronic wounds, have become an important problem that endangers human health. At present, there are many repair methods, and among them combines materials science and biology is one of the important repair methods. This study explored the preparation method, physicochemical properties, biological activity and safety of Platelet-Rich plasma (PRP)-loaded slow-sculpting graphene oxide (GO) / alginate gel, and applied it to acute full-thickness skin defect wounds in rats to observe its role in wound healing. The results show that the slow-sculpting GO / alginate gel has excellent plasticity and is suitable for a variety of irregularly shaped wounds. At the same time, its porous structure and water content can maintain the activity of platelets and their released growth factors in PRP, thereby promoting wound collagen synthesis and angiogenesis to accelerate wound healing. This indicates that the slow-sculpting GO / alginate gel is an excellent loading material for PRP, and the combination of the two may become one of the methods to promote wound repair.